Dynamics of Hepatitis B infection prevention practices among pregnant women attending antenatal care at Lubaga Hospital Kampala, Uganda using the constructs of information-motivation-behavioural skills model - Ismail Bamidele Afolabi; Abdulmujeeb Babatunde Aremu; Lawal Abdurraheem Maidoki; Nnodimele Onuigbo Atulomah (BMC, 2022)
Abstract Background Hepatitis B virus (HBV) infection is considered a significant global public health challenge with infectivity as well as estimated potential for transmission more than 50 to 100 times that of HIV. Over time, numerous empirical studies have shown that majority of HBV-related yearly global deaths are secondary to carcinoma of the liver. It is also known that HBV infected Women have the potential to transmit the infection vertically to their infants during pregnancy. This accounts for the WHO reported 3.16% prevalence among children less than 5 years of age in Uganda. This study assessed the predictors of HBV infection prevention practices among eligible consenting pregnant women using Lubaga health facility for antenatal care (ANC). Methods A cross-sectional descriptive study employing quantitative data collection based on the constructs of IMB model was used to capture data on the study variables among 385 randomly selected eligible pregnant women attending antenatal care at Lubaga hospital between September 2020 and October 2020. Data derived from the quantitative instrument was analysed by data reduction and transformation to summaries of descriptive statistics using (SPSS version 26) and regression analysis was performed to establish characteristics of the association between the variables with significance level set as (p < 0.05). Chi-square goodness-of-fit test was employed for significant differences in the proportion of dichotomous responses. Results The findings showed that more than half of the respondents (59%) were between the ages of 18 and 28 and majority of them (42.3%) had secondary education. Furthermore, an average but inadequate knowledge ( $$\overline{X }=$$ X ¯ = 5.97 ± 6.61; B = 0.57; p < .001), positive perception ( $$\overline{X }=$$ X ¯ = 17.10 ± 18.31; B = 0.97; p = .014) and good behavioural skills ( $$\overline{X }=$$ X ¯ = 12.39 ± 13.37; B = 0.56; p < .001) for adopting prevention practices all statistically predicted the averagely acceptable level of prevention practices ( $$\overline{X }=$$ X ¯ = 15.03 ± 16.20) among the study respondents as measured on rating scales of 12, 33, 21 and 30 respectively. Conclusion and recommendation There were observed gaps in their knowledge about some basic features of the infection like transmission and risk factors as well as some misperceptions about vaccination despite the relatively average score level for both, which is likely to influence their prevention behaviours and predispose them to the risk of the infection if actions are not taken. Therefore, personalized health education is needed during antenatal visits and subsequent health campaign in order to inform better prevention practices among this vulnerable population group.